Novel Green Approach for Synthesis of Metallic Nanoparticles and its Biomedical Application - Majeed, Shahnaz; Joel, Elsa L.; Hasnain, M.S. (Current Nanomedicine, 2018)
Nanotechnology is the recent promising area which controls the matters at nanoscale level ranging from 1–100 nm, especially dealing with nanoparticles. These nanoparticles can be manufactured by using various approaches like physical, chemical approach which time is consuming, using of toxic chemicals and required lot of energy to synthesize. However, the biological method by using various biological organisms like bacteria, fungi and plant as nanofactories is very simple to handle, easily available and less toxic. These nanoparticles had a broad range of applications in various sectors of life, especially in the medical field. Present review gives some various biological resources which are environmental friendly for the production of nanoparticles and their potential application in various areas of life sector.
Keywords: nanotechnology